2017
DOI: 10.1159/000481986
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nickel Release from Endobronchial Valves as a Possible Cause of Hypersensitivity Pneumonitis in a Patient Treated with Bronchoscopic Lung Volume Reduction

Abstract: Background: Endobronchial valve (EBV) placement is an established lung volume reduction procedure aiming to improve lung function and exercise capacity in patients with severe emphysema. As EBVs consist of silicone and nitinol (a metal alloy of nickel and titanium), there are concerns that nickel ions might be released and could have a clinical impact in patients with a contact allergy to nickel. Based on a case with hypersensitivity pneumonitis (HP) after treatment with EBVs, we aimed to evaluate the in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…To date, only one in vitro study has assessed the release of nickel ions from EBVs. This study found a significant release of nickel in the first 48 hours, which did remain below the toxic level (for oral intake of nickel) [7]. However, it remains unknown if these results resemble the in vivo situation, especially because the implantation environment can influence the amount of nickel that can leach from nitinol devices.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…To date, only one in vitro study has assessed the release of nickel ions from EBVs. This study found a significant release of nickel in the first 48 hours, which did remain below the toxic level (for oral intake of nickel) [7]. However, it remains unknown if these results resemble the in vivo situation, especially because the implantation environment can influence the amount of nickel that can leach from nitinol devices.…”
Section: Introductionmentioning
confidence: 59%
“…Furthermore, the nitinol frame of EBVs is mostly covered by silicone, preventing nickel ion release, which is not the case with Amplatzer septal occluders. However, it has been shown that the surface area of the EBV is not always completely covered with silicone [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Endobronchial valves are composed of a duck-bill unidirectional valve attached to a nitinol frame. All components are either composed of, or covered by silicone [29] . Silicone and nitinol have good biocompatibility profiles [ 5 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, care providers must be aware of potentially fatal complications, such as post-valvular pneumonia with septic shock (Figure 1) or severe hemoptysis with subsequent respiratory failure ( Figure 2). Recently, a case of severe hypersensitivity pneumonitis in a patient with Nickel allergy treated with endobronchial valves (15). In addition, the authors detected loss of Nickel ions from valves in in vitro experiments.…”
Section: Complications After Valve Treatmentmentioning
confidence: 99%